Relación entre el liderazgo y el síndrome del burnout antes y durante la pandemia COVID-19 - Caillaux Montes, Sophie (2022)
In recent years, leadership management in organizations has taken on a significant role in the achievement of organizational objectives, due to its impact on the behaviour of work teams. In contexts of change and uncertainty, such as the COVID-19 pandemic, organizations are forced to adapt to the needs of the environment while maintaining the same levels of productivity. Under these conditions, they can expose their employees to high standards of demand, putting their mental health at risk. As a result, workers may experience high levels of stress and exhaustion, and may develop Burnout Syndrome. The objective of this review is to identify the relationship between Leadership and Burnout during the COVID-19 pandemic. Based on the guidelines established by the PRISMA guide (Urrútia & Bonfill, 2021), an applied review of scientific articles in Ebsco and Proquest databases was carried out. Twelve full-text publications were selected for the analysis. Likewise, the findings show that the type of relationship between the variables involved will be affected by the leadership employed.